Insurgency and Small Wars: Estimation of Unobserved Coalition Structures. Issue 2 (25th March 2019) - Trebbi, Francesco; Weese, Eric
Abstract : Insurgency and guerrilla warfare impose enormous socio‐economic costs and often persist for decades. The opacity of such forms of conflict is an obstacle to effective international humanitarian intervention and development programs. To shed light on the internal organization of otherwise unknown insurgent groups, this paper proposes two methodologies for the detection of unobserved coalitions of militants in conflict areas. These approaches are based on daily geocoded incident‐level data on insurgent attacks. We provide applications to the Afghan conflict during the 2004–2009 period and to Pakistan during the 2008–2011 period, identifying systematically different coalition structures. Applications to global terrorism data and identification of new groups or shifting coalitions are discussed.